Enterprise Systems Engineering for Better Operational Interoperability. Issue 6 (21st January 2016) - Sitton, Miri; Reich, Yoram
ABSTRACT: During the last decades, many enterprises have transformed to technology based organizations. However, in order to manage this transformation, technology‐intensive enterprises have to deal with new opportunities and threats that the information age has created. Many enterprises use a wide range of heterogeneous systems and networks to support a variety of users. In practice, the development and operation of these heterogeneous systems is usually distributed and unsynchronized, although operational interoperability and system integration are required to support cross‐enterprise processes and decision making. Enterprise systems engineering (ESE) processes can provide the opportunity to deal with these new challenges of achieving better operational interoperability as well as system interoperability. Our basic claim is that ESE differs significantly from systems engineering (SE). This paper identifies the differences between them and discusses complex emerging challenges of ESE. Our contribution in this paper is to identify relevant state of the art research and practice frontier in ESE that are closest to meet ESE challenges and clarify existing gaps. By recognizing the gaps in existing methods, we define a foundation for a new approach to address these gaps. The main realization of this research involves the need to use systems engineering methodologies, tailored to, and driven from, the enterprise specific operational processes, to improve the effectiveness of these processes, as part of the enterprise strategy.